A feature-based anthropometry for garment industry - Leong, Iat-Fai; Fang, Jing-Jing; Tsai, Ming-June (International journal of clothing science and technology, 2013)
Purpose - The purpose of this paper is to propose a method to automatically generate individualized body size measurements from cloud point of a body scanner. It aims to propose a fast, reliable, and unambiguous method to obtain human body measurements for use in the garment industry.Design methodology approach - Based on a previous study by the authors, geometric features on the scanned body are identified by computerized algorithms through mathematical definitions. Feature lines situated on the human body surface are created as polylines that pass through the body's features and three types of computer measurements (tape-measurement, contour-measurement, and linear-measurement) are provided.Findings - By dividing the body surface into rectangular patches using the feature lines as boundaries, the body can be reconstructed easily with a minimal amount of triangles while retaining the essential shape. The proposed measuring method applies to most manual measurements used in the garment industry. The authors evaluated the anthropometry variations of the same subject to explore the reliability of the proposed method. It was found that the precision of the method is well below the standard requirement of the traditional manual method.Research limitations implications - In this research, subjects were scanned in standing pose; this pose minimizes regions obstructed by body parts and permits maximal acquisition of as many key landmarks. Since the features are identified by geometric analysis without the need for marker attachment, measurements of the required sitting position are impossible to obtain in the current study.Originality value - Resolution of meshing can be changed according to application requirements. Contrary to the traditional manual method, efficiency and precision are the advantages of the present method.